DETERMINATION OF OPTIMUM INSULATION THICKNESS BY USING HEATING AND COOLING DEGREE-DAY VALUES - Ozel, Meral; Pihtili, Kazim (Yildiz Technical Univ, 2008)
In this study, optimum thickness of insulation applying to external walls was determined by considering heating and cooling degree day values. Calculations were done for Adana, Elazig, Erzurum, Istanbul ve Izmir cities. In this case, optimum insulation thickness, energy saving and pay back period was calculated by applying Extruded polystyrene as insulation material on the external walls. As result, it was showed that optimum insulation thicknesses vary between 0.04 and 0.084 m, energy savings between 21.94 and 97.12 YTL/m(2), and payback periods between 1.45 and 2.05 years to the city investigated
Keywords: Insulation thickness; heating and cooling degree-day values; energy saving; payback period